Analisis Determinan Kepuasan Pelanggan Pada Hotel Wyndham OPI Palembang - Andre Yohanes; Herry Widagdo (Universitas Multi Data Palembang, 2026)
This study aims to analyze the determinants of customer satisfaction at Wyndham OPI Palembang Hotel involving four factors, namely service quality, price, brand image, and customer experience. A quantitative approach was employed using a questionnaire based survey. Data were collected from 220 hotel guests who had stayed at least twice through purposive sampling. The data were analyzed using multiple linear regression. The results indicate that service quality, price, and customer experience have a positive and significant effect on customer satisfaction, while brand image has no significant effect. Simultaneously, all independent variables have a significant effect on customer satisfaction. These findings suggest that customer satisfaction in star-rated hotels is influenced by service related aspects, pricing, and overall customer experience.